Minimally Invasive Surgical Approach to Complicated Recurrent Pilonidal Sinus - Vahit Onur Gul; Sebahattin Destek; Serhat Ozer; Ergin Etkin; Serkan Ahioglu; Mehmet Ince; Vedat Cimin; Deniz Sen; Yesim Erbil (Case Reports in Surgery)
Pilonidal sinus is considered as a simple and frequently occurring disease localized at the sacrococcygeal area. However, at the intergluteal region, it can often turn into a chronic and complicated disease. In some cases, it can fistulize up to the gluteal region and appear at the secondary orifices. Minimally invasive surgical techniques are becoming widespread in recent years due to the increased experience and development of new instruments. Limited excision of the pilonidal sinus tract can be a better treatment option compared with large excisions in terms of recovery time and patient’s comfort. This case study reports the single-phase surgical treatment of complicated and recurrent pilonidal sinus localized at the gluteal area, with minimal tissue loss and inflammation.